2020
DOI: 10.1016/j.apcatb.2019.118031
|View full text |Cite
|
Sign up to set email alerts
|

Thin film electrodes from Pt nanorods supported on aligned N-CNTs for proton exchange membrane fuel cells

Abstract: The enhanced performance of carbon nanotubes (CNTs) over carbon black as a catalyst support and the outstanding catalytic activities of one-dimensional (1D) Pt nanostructures endow them big potential for applications in fuel cells. However, the research has been mainly focused on the materials, and a combination of both 1D Pt nanostructures and CNTs to fabricate practical high power performance fuel cell electrodes still remains a challenge. In this work, we demonstrate catalyst electrodes from Pt nanorods gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…>The superior stability of 1D Pt nanostructured catalysts in PEMFCs has been widely reported in the literature. 14,42,48,49 However, further approaches to enhance the catalytic activity of the 1D Pt nanostructures through alloying remain a challenge because of the stability issue of the alloyed metals. 8 Our previous studies demonstrated a more pronounced degradation mechanism of the bimetallic 1D Pt nanostructures hybridized with Ag and Ni, 24,50 induced by the atomic segregation and susceptibility of the transition metals to oxidation in electrochemical reaction under acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…>The superior stability of 1D Pt nanostructured catalysts in PEMFCs has been widely reported in the literature. 14,42,48,49 However, further approaches to enhance the catalytic activity of the 1D Pt nanostructures through alloying remain a challenge because of the stability issue of the alloyed metals. 8 Our previous studies demonstrated a more pronounced degradation mechanism of the bimetallic 1D Pt nanostructures hybridized with Ag and Ni, 24,50 induced by the atomic segregation and susceptibility of the transition metals to oxidation in electrochemical reaction under acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the ultralow loading can reduce the catalyst cost, there are still big challenges to realize a real high-power-density operation. In view of this drawback, Du's group [115] designed CLs from 1D Pt catalysts deposited on VACNTs by a facile wet chemical method. With a catalyst loading of 0.19 mg Pt / cm 2 , the electrode showed 23% higher power density at 0.6 V than that of a Pt/C (TKK, 45.9 wt%) electrode with a catalyst loading of 0.41 mg Pt /cm 2 .…”
Section: Ordered Catalyst Support Structurementioning
confidence: 99%
“…e) Reproduced with permission. [197] Copyright 2019, Elsevier. f) Conventional membrane electrode assembly (MEA) with a catalyst-coated membrane (CCM) and modified MEA with an inverse-opalstructure (IO) electrode.…”
Section: Correlation Between 3d Confinement and Electrocatalytic Perfmentioning
confidence: 99%
“…[196] For example, short Pt nanorods were grown on carbon nanotubes (Pt/N-CNTs), which were fabricated by plasma enhanced chemical vapor deposition and nitride active screen plasma treatment on carbon paper gas diffusion layers. [197] Since Pt/N-CNTs for a thin open catalyst layer, they enhance the mass transfer performance, as shown in Figure 3e, achieving 1.23-fold enhanced power density in a polymer electrolyte membrane fuel cell (PEMFC) using less than half of the Pt loading compared to commercial Pt/C. Moreover, FC having inverse opal (Figure 3f) as the oxygen electrode generated outstanding power densities at higher overpotential (<0.7 V), compared to the conventional device .…”
Section: More Efficient Mass Transport In 3d-ordered Electrocatalystsmentioning
confidence: 99%